2010
DOI: 10.1007/s11783-010-0261-7
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin-LR biodegradation by Sphingopyxis sp. USTB-05

Abstract: A promising bacterial strain for biodegrading microcystin-LR (MC-LR) as the sole carbon and nitrogen source was successfully isolated from Lake Dianchi, China. The strain was identified as Sphingopyxis sp. USTB-05, which was the first isolated MCs-biodegrading Sphingopyxis sp. in China. The average biodegradation rate of MC-LR by Sphingopyxis sp. USTB-05 was 28.8 mg$L -1 per day, which was apparently higher than those of other bacteria reported so far. The optimal temperature and pH for both strain USTB-05 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
(66 reference statements)
2
14
0
Order By: Relevance
“…Finally the fourth enzyme peptidase cleaved the peptide bond of Tyr-Masp in the linear tripeptide of Tyr-Masp-Arg, and Tyr ( m/z 181) (product D) and dipeptide (Masp-Arg) ( m/z 268) were produced ( Fig 8 ). Generally, the biodegradation pathway of MC-YR was very similar to that of MC-RR and MC-LR in the first three steps we have reported previously [ 18 , 19 ], [ 28 , 29 ]. Here we firstly provided direct evidence that the tripeptide of Tyr-Masp-Arg could also be further biodegraded, and Tyr was produced as a biodegradation product of MC-YR (Fig 3 and 8 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Finally the fourth enzyme peptidase cleaved the peptide bond of Tyr-Masp in the linear tripeptide of Tyr-Masp-Arg, and Tyr ( m/z 181) (product D) and dipeptide (Masp-Arg) ( m/z 268) were produced ( Fig 8 ). Generally, the biodegradation pathway of MC-YR was very similar to that of MC-RR and MC-LR in the first three steps we have reported previously [ 18 , 19 ], [ 28 , 29 ]. Here we firstly provided direct evidence that the tripeptide of Tyr-Masp-Arg could also be further biodegraded, and Tyr was produced as a biodegradation product of MC-YR (Fig 3 and 8 ).…”
Section: Discussionsupporting
confidence: 79%
“…It was found that Sphingopyxis sp. USTB-05 possessed at least three enzymes involved in biodegradation of MC-LR and MC-RR, and three biodegradation genes have been firstly cloned and expressed [ 18 , 19 ], [ 28 , 29 ]. Compared with MC-RR and MC-LR, MC-YR is more complicated in structure containing a benzene ring of Tyr, which could also be rapidly biodegraded by CEs of Sphingopyxis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingopxyis sp. USTB-05 showed complete MCs (MC-LR, MC-RR and MC-YR) degradation with different intermediate products [30,[118][119][120][121]. These findings suggest that the enzymatic processes and degradation pathways may vary between MC variants and bacteria strains.…”
Section: Enzymatic Mechanisms Of Microcystins Biodegradationmentioning
confidence: 83%
“…A large array of MCs-degrading bacteria, both containing and lacking mlr genes, have been isolated from both water and sediment samples. Most of these strains belong to the phyla Proteobacteria (especially classes α- and β-Proteobacteria) [25,26,27], although strains from the phyla Actinobacteria and Firmicutes have also been reported [23,28]. …”
Section: Introductionmentioning
confidence: 99%